Respuesta :
Answer:
46^6 x 59^6
Step-by-step explanation:
For properties (axb)^y has the equivalent expression of a^y x b^y
Then, (46x59)^6 can be written as 46^6 x 59^6
Answer: [tex]46^6* 59^6[/tex]
Step-by-step explanation:
Given the expression [tex](46* 59)^6[/tex], in order to find an equivalent expression using the same bases, you need to remember the following:
[tex](a*b)^n=a^n*b^n[/tex]
So, you can observe that, in this case:
[tex]a=46\\b=59\\n=6[/tex]
Therefore, substituting values, you get the following equivalent expression:
[tex](46* 59)^6=46^6* 59^6[/tex]